1985
DOI: 10.1246/cl.1985.385
|View full text |Cite
|
Sign up to set email alerts
|

Firm Evidnce for Cis-Aminopalladation in the Reaction of 1-Aminohexatrienes With Palladium Dichloride

Abstract: The reaction of PdCl2(PhCN)2 with ethyl α-N-acetyl-β-(4,6-dimethylbenzofuran-2-yl)acrylate, having a Z-propenyl group at 2-position of benzofuran ring, gave an azepine derivative, whereas its E-isomer afforded a Pd-σ-complex having azepine skeleton. Configurational assignment of the σ-complex, accomplished by methoxycarbonylation, clearly demonstrates that this intramolecular aminopalladation proceeds via cis-aminopalladation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Treatment of the isolated aminobrominated intermediate 5 with base in DMF gave the expected product 3a as single isomer in 92% isolated yield. This reaction outcome suggests that the present diamination reaction proceeds through a catalytic cycle of syn -aminopalladation ,,,, to A followed by copper-mediated transient palladium oxidation with concomitant C–Br bond formation . This latter step proceeds with clean S N 2 chemistry leading to inversion of configuration at carbon.…”
Section: Resultsmentioning
confidence: 72%
“…Treatment of the isolated aminobrominated intermediate 5 with base in DMF gave the expected product 3a as single isomer in 92% isolated yield. This reaction outcome suggests that the present diamination reaction proceeds through a catalytic cycle of syn -aminopalladation ,,,, to A followed by copper-mediated transient palladium oxidation with concomitant C–Br bond formation . This latter step proceeds with clean S N 2 chemistry leading to inversion of configuration at carbon.…”
Section: Resultsmentioning
confidence: 72%
“…31a Later, a report by Taniguchi and co-workers showed that enamide 46 underwent aminopalladation to furnish isolable Pd-alkyl intermediate 47 (eq 6). 33 The anti relationship between Pd and the β -hydrogen precludes β -hydride elimination from occurring, and the product stereochemistry supports a cis -aminopalladation mechanism. These early studies, which established a foundation for future investigations of alkene amination, were based upon stoichiometric reactions and therefore the insights do not necessarily apply to catalytic systems.…”
Section: Mechanistic Studies Of Nucleopalladationmentioning
confidence: 96%
“…Evidence for trans attack of the coordinated alkene was provided by formation of cyclometalated Pd−alkyl intermediate 44 , whose stereochemistry was established by NMR spectroscopic studies or by reduction with LiAlD 4 to form stereospecifically deuterated product 45 (Scheme ) . Later, a report by Taniguchi and co-workers showed that enamide 46 underwent aminopalladation to furnish isolable Pd−alkyl intermediate 47 (eq ) . The anti relationship between Pd and the β-hydrogen precludes β-hydride elimination from occurring, and the product stereochemistry supports a cis -aminopalladation mechanism.…”
Section: Mechanistic Studies Of Nucleopalladationmentioning
confidence: 98%
“…The first amidopalladation, analogous to alkoxypalladation, was explored in a stoichiometric experiment with enamide 116 and found to produce the azepine derivative 117 with the new C=N and C=Pd bonds related in a cis -fashion, which correspond to syn -addition (Scheme 31). [ 50 ]…”
Section: Intramolecular Amidopalladationmentioning
confidence: 99%